2020
DOI: 10.1111/fwb.13509
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fishes on macroinvertebrate communities and insect emergence production in intermittent stream refuges

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 87 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…A DNA-based MSAM could therefore improve our understanding of phenology for whole communities, temporal partitioning among functional groups, as well as the potential value of abundance information for construction of ecological networks (Freilich et al, 2018). The exclusion treatment represents a dramatic change in ecological interaction strengths and confirmed that direct fish predation can significantly depress average invertebrate abundance in the stream (Bonjour et al, 2020;Dudgeon, 1991;Williams et al, 2003;Winkelmann et al, 2011). Cages inherently alter microhabitat factors, such as flow and shading, but our Open control cages were designed to account for those confounding effects.…”
Section: Discussionmentioning
confidence: 81%
“…A DNA-based MSAM could therefore improve our understanding of phenology for whole communities, temporal partitioning among functional groups, as well as the potential value of abundance information for construction of ecological networks (Freilich et al, 2018). The exclusion treatment represents a dramatic change in ecological interaction strengths and confirmed that direct fish predation can significantly depress average invertebrate abundance in the stream (Bonjour et al, 2020;Dudgeon, 1991;Williams et al, 2003;Winkelmann et al, 2011). Cages inherently alter microhabitat factors, such as flow and shading, but our Open control cages were designed to account for those confounding effects.…”
Section: Discussionmentioning
confidence: 81%
“…Southern redbelly dace and central stonerollers (hereafter referred to as redbelly dace and stonerollers) are two small cyprinids that impact structural (algal filament length, organic matter) and functional (stream metabolism) properties of streams (e.g., Bengtson et al., 2008 ; Bertrand & Gido, 2007 ; Bonjour et al., 2020 ; Gelwick & Matthews, 1992 ; Martin et al., 2016 ; Power & Matthews, 1983 ). Few studies have directly analyzed the relationship of fish size and their influence on stream ecosystem properties.…”
Section: Introductionmentioning
confidence: 99%